Critical Success Factors Of Implementing Web Interface Management System For Subsea Projects - Marimuthu, Suresh Kumar (2011)
This research outlines on the critical success factors which could be achieved and experienced from the implementation of web interface management system (WIMS) in subsea projects. WIMS will provide a systematic platform for the subsea project to manage project interfaces and execute their task easily, efficient and effectively without facing major problems.The WIMS can be defined as an electronic database that allows internal disciplines and external third parties to clarify any issues regard to subsea projects.